The impacts of oral contraceptives on the female body: an integrative literature review (Research, Society and Development, 2023)
Introduction: Oral contraceptives are medications composed of synthetic hormones that can be used for contraception or to treat some pathologies, thus directly interfering with the woman's endocrine system. Objective: This study aims to search the databases for current scientific information on the impact of contraceptives on the endocrine system and thus contribute to academic studies on this subject. Methodology: this is a descriptive research, of the integrative literature review type, carried out through online access to the National Scientific Electronic Library Online (Scielo), Google Scholar and National Library of Medicine (PubMed MEDLINE) databases, in the months of August and September 2022. Results and discussion: Contraceptives meant a great advance in women's health, and this is the most used reversible method in Brazil. These drugs can be of the combined or mini-pill type, the combined are divided into first, second, third and fourth generation, these being monophasic, biphasic or triphasic. The combined form is the one with the highest risk of adverse effects right after the first dose and in the long term, such as headache, mastalgia or breast pain, dizziness, nausea, vomiting, mood changes, anxiety and depression disorders, headache, drop in libido, breast enlargement, fluid retention and weight gain. Therefore, an adequate prescription is needed to obtain the benefits of the medication, avoiding the risks of side effects. Conclusion: Contraceptives are efficient and are a good alternative for fertility control, treatment of diseases such as Polycystic Ovary Syndrome and dysmenorrhea, but due to the hormonal changes caused by these drugs, it is necessary to follow up with a professional to ensure safe use for patients.